2021
DOI: 10.1155/2021/9013280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Marginal Zinc Deficiency on Development, Redox Status, and Gene Expression Related to Oxidation and Apoptosis in an Avian Embryo Model

Abstract: Maternal severe zinc (Zn) deficiency resulted in growth retardation and high mortality during embryonic development in human. Therefore, this study is aimed at evaluating the effect of maternal marginal Zn deficiency on the development and redox status to avoid severe Zn deficiency using an avian model. A total of 324 laying duck breeders at 214 days old were randomly allotted into 3 dietary Zn levels with 6 replicates of 18 ducks per replicate. The birds were fed experimental diets including 3 dietary supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Restricting our analysis to mRNA expression is a clear limitation of this study. Since the data shown for zinc transporters and MT presented here ( Figure 1 , Figure 2 and Figure 3 ) match well with major findings regarding zinc metabolism in other species [ 9 , 19 , 31 , 39 ], the validity of our data is still probably high. Unfortunately, the available resources for studying zinc transporters and zinc-related processes in Asian sea bass on a molecular level are so far limited.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Restricting our analysis to mRNA expression is a clear limitation of this study. Since the data shown for zinc transporters and MT presented here ( Figure 1 , Figure 2 and Figure 3 ) match well with major findings regarding zinc metabolism in other species [ 9 , 19 , 31 , 39 ], the validity of our data is still probably high. Unfortunately, the available resources for studying zinc transporters and zinc-related processes in Asian sea bass on a molecular level are so far limited.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, CAT activity was increased in the heart of zinc deficient rats and a slight increase in the activity of SOD was observed as well [ 47 ]. Embryos from zinc deficient ducks revealed higher expression and activities of CAT [ 39 ]. Moreover, thermal or nutritional stress significantly increased SOD mRNA and CAT levels in the tropical fish species Chanos chanos [ 48 ] and in plasma of Starry flounder [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on fish reported that supplementation with Cu nanoparticles increased GPx, SOD and CAT activities and decreased MDA levels [ 50 ]. Gao et al found a positive correlation between plasma Zn content and GPx activity and a negative correlation between plasma Zn content and MDA content [ 51 ]. However, other authors negatively related serum Zn to GPx and positively to SOD and found no significant relationship with CAT and MDA content, whereas serum Cu content positively relates to GPx and negatively relates to SOD and CAT; no significant relationship with MDA was found [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies revealed that Zn as a cofactor of some distinct metalloenzymes is proposed to play a strong antioxidant role to restore mitochondrial oxidative damage [ 8 ]. Maternal Zn deficiency induces oxidative damage in liver resulting in embryonic development stagnation in the chick [ 9 ], duck [ 10 ] and mice [ 11 ]. Some studies have explored that maternal Zn supplementation could enhance the synthesis of hepatic metallothionein (MT) in offspring embryos [ 12 ], which is relevant in scavenging the excessive mitochondrial ROS generation under stressful conditions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%